Development of different herbaceous perennial species on the experimental extensive green roof of Corvinus University Budapest - Fejes, Zs.; Gerzson, L. (International Journal of Horticultural Science, 2006)
During 2003-2004 six "traditional" herbaceous plant species (Sedum reflexum, Sedum acre ’Aureum’, Sedun spurium„Sedum floriferum, Festuca glauca) and six "new" plant species (Sedum pulchellum, Prunus tenella, fivericum polyphyllum, CeraiTtignIct plumbaginoides, Dianthus plumarius and Phlox subulala) were tried on four different types of roof insulation on the 100 m large experimental extensive green roof of the Building K of Corvinus University Budapest, at Villányi street, Budapest. According to the results obtained so far, the viability and good decoration values of all the "traditional" plants were proved. From the six "new" plants Ceratostigma plumbaginoides, Dianthus plumarius and Sedum pulchellum (with some restrictions) proved to be suitable. A significantly poorer development was showed by the remaining "new" species (Phlox subulata, 1-1yericum polyphyllum, Prunus tenella) than the "traditional" ones. As for the different types of roof insulation, the best was with the direct order of layers, and drainage layer with water storage capacity.